Tissue-Resident Macrophages Limit Pulmonary CD8 Resident Memory T Cell Establishment - Goplen, Nick P.; Huang, Su; Zhu, Bibo; Cheon, In Su; Son, Young Min; Wang, Zheng; Li, Chaofan; Dai, Qigang; Jiang, Li; Sun, Jie (Frontiers in Immunology, 2019)
Abstract Tissue resident memory CD8 T cells (TRM) serve as potent local sentinels limited to previous sites of inflammation and their draining lymph nodes. TRM contribute significantly to protective immunity against previously encountered intracellular mucosal pathogens. While the molecular and transcriptional underpinnings of TRM differentiation are emerging, how TRM establishment is regulated at the cellular level by other immune cell types in vivo is largely unclear. Here, we observed that the expression of PPAR-γ in the myeloid compartment was a negative regulator of CD8 TRM establishment following influenza virus infection. Interestingly, myeloid deficiency of PPAR-γ resulted in selective impairment of tissue-resident alveolar macrophage (AM) compartment during primary influenza infection, suggesting that AM are likely negative regulators of CD8 TRM differentiation. Indeed, influenza-specific CD8 TRM cell numbers were markedly increased following early, but not late ablation of AM using the CD169-DTR model. Importantly, these findings were specific to the infected tissue as circulating memory T cell frequencies in lung and spleen were unaltered following macrophage ablation. These data reveal a tissue-specific innate cellular network involved in locally regulating the programming of TRM differentiation. Such knowledge could aid in vaccine design aimed at increasing TRM density to enhance protective immunity, or deflating their numbers in conditions where they cause overt or veiled chronic pathologies.